Bantara:Aplikasi Permainan Interaktif Belajar Membatik Motif Batik Nusantara Berbasis Android - Handoko, Slamet; Suyanto, Budi; Karoma, Ahmad Yusuf (JTET (Jurnal Teknik Elektro Terapan), 2017)
Batik is one of the cultural heritage that has been designated by UNESCO as a Cultural Heritage Humanitys Oral and Non-material Masterpieces of the Oral and Intangible Heritage of Humanity) since October 2009. Art Batik is the art over the cloths to clothe the beginning only used by the family empires only. The advancement of science in the field of information and communication technology, especially the use of handheld devices Android smartphone has changed the perspective and lifestyle in carrying out daily activities. This impacted on the traditional arts activities. The less the interest of the public to learn or just know about the background of this application that combines the advancement of science in the field of technology to load content that is traditional kinds of batik to preserve it. This application is made into an interactive educational game flash format using Adobe software Animate CC and is designed to run on the Android operating system.Keywords: Android,Â  Batik, Flash, Interaction Game